THE EFFECT OF INFORMATION ASYMMETRY ON EARNINGS MANAGEMENT THROUGH ACCRUAL AND REAL ACTIVITIES DURING GLOBAL FINANCIAL CRISIS - Lodovicus Lasdi (Universitas Hayam Wuruk Perbanas, 2013)
This study examines the impact of the 2008-2009 financial crisis on the earnings managementbehavior of Indonesian listed firms. This study gives evidence of how the presence of informationasymmetry affects management incentives to manage earnings, especially through real activities.When information asymmetry is high, stakeholders do not have sufficient resources, incentives oraccess to relevant information to monitor manager’s actions, which gives rise to the practice ofearnings management. This research replicate the work of Richardson (2000) and Rahmawatiand Baridwan (2006) but in the setting of during global financial crisis. This study examines theeffect of SarbOx on earnings management behavior and shows that earnings management hasshifted from accrual management to real account management. Using 55 manufacturing firmsfrom 2008 to 2011, this study adds to our knowledge of earning management and informationasymmetry during global financial crisis in Indonesia.